Effect of Pomegranate Fruit Juice and Seed Oil on Serum Lipid Levels and Atherosclerosis Development in Hypercholesterolemic Rabbits - T Radjabian; H Fallah Husseini; M Karami; I Rasooli; S Faghihzadeh (Institue of Medicinal Plants, ACECR, 2008)
Background: Pomegranate (Punica granatum L.) is a drought tolerant fruit-bearing deciduous shrub native to Iran. It is widely cultivated in dry areas of Iran. Pomegranate fruit juice contains a wide range of polyphenolic metabolites, especially punicalagins with powerful antioxidative properties. Pomegranate seed oil is a unique natural product and a rich source of conjugated fatty acids. Objective: The aim of this study was to investigate the pharmacological effects of fruit juice and seed oil of pomegranate on serum lipid levels of hypercholesterolemic rabbits and development of atherosclerosis on their aortas. Methods: Fourthly two males and six months aged white New Zealand rabbits (1.7 -2 kg) were randomly assigned to six equal groups and caged in the same environmental condition. One group was fed on regular animal house rabbit chew. Five other groups fed with high cholesterol diet (1% cholesterol). One group kept as control and other 4 groups fed on same diet supplemented with 1% and 2% doses of pomegranate fruit juice or seed oil. The whole experiment lasted 2 months. At the end of the study (after 2 months) the biochemical analysis of serum lipids and pathological evaluation of atherosclerotic plaque of aortas were performed. Results: Results of biochemical analyses showed that administration of fruit juice and seed oil at both doses did not significantly affect the level of serum lipids profile of hypercholesterolemic rabbits. Pathological data analysis showed that treatments of rabbits with fruit juice and seed oil at both doses significantly reduced aortic atherosclerotic plaque formation. Conclusion: Pomegranate fruit juice and seed oil administration inhibited atherosclerosis development in hypercholesterolemic rabbit's aortas without any significant effects on lipid profile.